Sustainable intensification of agri-food systems in the Indo-Gangetic Plain: Intensification with potato promises increased income and food security, but trade-offs must be considered - International Potato Center (International Potato Center, 2020)
Sustainable intensification invariably results in social, economic, and environmental trade-offs. The most obvious is the one between producing more food on the same area of land and minimizing the environmental degradation required for that additional production. If potato is added to a rice-based system, what additional inputs are needed and what will be their environmental impact? From this starting point, the researchers sought to fulfill two objectives: 1. To understand better the potential for SI of rice-based systems with potato in the Eastern Indo-Gangetic Plains; and 2. To examine the effects of SI on farming inputs and outputs.